2017
DOI: 10.1038/srep46303
|View full text |Cite
|
Sign up to set email alerts
|

Preference for facial averageness: Evidence for a common mechanism in human and macaque infants

Abstract: Human adults and infants show a preference for average faces, which could stem from a general processing mechanism and may be shared among primates. However, little is known about preference for facial averageness in monkeys. We used a comparative developmental approach and eye-tracking methodology to assess visual attention in human and macaque infants to faces naturally varying in their distance from a prototypical face. In Experiment 1, we examined the preference for faces relatively close to or far from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 95 publications
(136 reference statements)
1
18
0
Order By: Relevance
“…We found that human infants looked longer and had more fixations on average than macaque infants, suggesting that human infants may have more sustained attention than macaque infants during the first year of life. Previous studies comparing human and macaque social attention (e.g., Damon et al., 2017; Guo, Li, Yan, & Li, 2019) have not directly compared species, as in the present study. In addition, we found that macaque infants spent proportionately more time looking to the social video compared to human infants, indicating that macaques’ relative interest in social stimuli may be greater than human infants’ relative interest in social stimuli, across the first year.…”
Section: Study 2: Human Infant Social Attention Developmentmentioning
confidence: 76%
“…We found that human infants looked longer and had more fixations on average than macaque infants, suggesting that human infants may have more sustained attention than macaque infants during the first year of life. Previous studies comparing human and macaque social attention (e.g., Damon et al., 2017; Guo, Li, Yan, & Li, 2019) have not directly compared species, as in the present study. In addition, we found that macaque infants spent proportionately more time looking to the social video compared to human infants, indicating that macaques’ relative interest in social stimuli may be greater than human infants’ relative interest in social stimuli, across the first year.…”
Section: Study 2: Human Infant Social Attention Developmentmentioning
confidence: 76%
“…All facial images were scaled and realigned based on eye size and position. To delineate the features of each face, 118 landmarks were placed for each facial image (see Supplementary Figure S1 ) with Psychomorph software 47 , which has been widely used to morph chimpanzee, capuchin monkey, rhesus macaque, and human faces 32 , 35 , 37 , 48 . To average adult and infant face images, we superimposed the adult facial images on one another and the infant facial images on one another.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that faces gazing directly at the viewer would receive the greatest attention compared to faces with averted eyes or heads (Prediction 1c), because these are the most prototypical faces (i.e., symmetrical, average angle; Damon et al, ; Slater et al, ). However, we found that human faces with averted heads and averted eyes received the most attention.…”
Section: Discussionmentioning
confidence: 99%